2013
DOI: 10.1038/ncomms2995
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of 5-hydroxymethylcytosine during mouse spermatogenesis

Abstract: Little is known about how patterns of DNA methylation change during mammalian spermatogenesis. 5hmC has been recognized as a stable intermediate of DNA demethylation with potential regulatory functions in the mammalian genome. However, its global pattern in germ cells has yet to be addressed. Here, we first conducted absolute quantification of 5hmC in eight consecutive types of mouse spermatogenic cells using liquid chromatographytandem mass spectrometry, and then mapped its distributions in various genomic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
210
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(226 citation statements)
references
References 55 publications
16
210
0
Order By: Relevance
“…In support of this hypothesis, 5hmC is present at the highest levels in gene bodies of the most highly expressed genes (43,(56)(57)(58)(59)(60), and TET proteins have been linked to many processes and histone modifications associated with transcriptional variability. (i) In yeast, the Set2 methyltransferase complex travels with RNA Pol II and methylates H3K36 in gene bodies; the H3K36me3 modification is recognized by the Sin3a/Rpd3 histone deacetylase (HDAC) complex, which permits nucleosome reassembly by deacetylating lysines on histones 3 and 4, thus preventing spurious initiation at intragenic sites (53).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In support of this hypothesis, 5hmC is present at the highest levels in gene bodies of the most highly expressed genes (43,(56)(57)(58)(59)(60), and TET proteins have been linked to many processes and histone modifications associated with transcriptional variability. (i) In yeast, the Set2 methyltransferase complex travels with RNA Pol II and methylates H3K36 in gene bodies; the H3K36me3 modification is recognized by the Sin3a/Rpd3 histone deacetylase (HDAC) complex, which permits nucleosome reassembly by deacetylating lysines on histones 3 and 4, thus preventing spurious initiation at intragenic sites (53).…”
Section: Discussionmentioning
confidence: 60%
“…(i) In yeast, the Set2 methyltransferase complex travels with RNA Pol II and methylates H3K36 in gene bodies; the H3K36me3 modification is recognized by the Sin3a/Rpd3 histone deacetylase (HDAC) complex, which permits nucleosome reassembly by deacetylating lysines on histones 3 and 4, thus preventing spurious initiation at intragenic sites (53). In mammalian cells, TET functions are linked to both types of histone modifications: high levels of 5hmC are present in the gene bodies of expressed genes; 5hmC distribution in gene bodies is strongly correlated with that of H3K36me3 (43,(56)(57)(58)(59)(60); and TET1 coimmunoprecipitates with SIN3A and HDAC1/2 in mouse ES cells (61). (ii) Also in yeast, H2B ubiquitylation has been implicated in nucleosome dynamics (54,55), and a screen for chromatin regulators that altered the variability of reporter expression in yeast showed that H2B ubiquitylation recruited the Set3C HDAC complex, thereby limiting the high rate of Pol II elongation associated with transcriptional bursts (49).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the cellular origin for the DEGs we used recently published datasets of genes that are expressed in different testicular cell types (87). We identified 349 DEGs out of 14 985 (total number of genes) that originate from spermatogonia (SG), 422 DEGs out of 16 562 from spermatocytes, 465 DEGs out of 21 856 in round spermatids and 411 DEGs out of total 17 081 genes from Sertoli cells (Supplementary Figure S12A).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that APA regulation is important for RNA processing during spermatogenesis (93). We compared APA transcripts with published datasets derived from different testis cell types (87) and found that the Cd68 APA transcript has altered 3′UTR. The change of 3′UTR in Cd68 APA transcript occurs during spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…5hmC enrichment over the gene body of highly expressed genes has also been noted in mouse ES cells (30), neuronal cells/ tissues (29), and differentiating sperm cells (44) (reviewed in ref. 9).…”
Section: Discussionmentioning
confidence: 99%